The association of vitamin D deficiency with psychiatric distress and violence behaviors in Iranian adolescents: the CASPIAN-III study. Issue 1 (December 2015) - Ataie-Jafari, Asal; Qorbani, Mostafa; Heshmat, Ramin; Ardalan, Gelayol; Motlagh, Mohammad; Asayesh, Hamid; Arzaghi, Seyed; Tajadini, Mohammad; Nejatinamini, Sara; Poursafa, Parinaz; Kelishadi, Roya
Abstract Background Subtle effects of vitamin D deficiency on behavior have been suggested. We investigated the association of vitamin D status with mental health and violence behaviors in a sample of Iranian adolescents. Methods This nationwide study was conducted in 2009–2010 in 1095 Iranian school students with mean age 14.7 ± 2.6 years. Items were adapted from the Global School-based Student Health Survey (GSHS). Psychiatric distress was considered as the self-reported anger, anxiety, poor quality sleep, confusion, sadness/depression, worry, and violence-related behaviors (physical fight, having bully, or getting bullied). Results Forty percent had serum 25(OH)D values below 10 ng/mL (vitamin D deficient), and 39 % had levels 10-30 ng/mL (vitamin D insufficient). The prevalence of self-reported anger, anxiety, poor quality sleep, sadness/depression, and worry was significantly lower (P  < 0.05) in vitamin D sufficient participants compared with their other counterparts. The odds of reporting anger, anxiety, poor quality sleep, and worry, increased approximately 1.5 to 1.8 times in vitamin D insufficient compared with normal children and adolescents (P  < 0.05). Risk estimates indicated that vitamin D insufficient and deficient subjects had higher odds of reporting worry compared to normal vitamin D group [OR = 2.417 (95 % CI: 1.483-3.940) for vitamin D insufficient students, and OR = 2.209 (95 % CI: 1.351-3.611) for vitamin D deficient students] (P-trend = 0.001). Violence behaviors did not show any association with vitamin D status (P  > 0.05). Conclusion Some psychiatric distress such as anger, anxiety, poor quality sleep, depression, and worry are associated with hypovitaminosis D in adolescents. The clinical significance of the current findings should be determined in future longitudinal studies.